Acute Gastroenteritis in the Etiology of Inflammatory Bowel Disease: Systematic Review and Meta-analysis. Issue 4 (1st October 2021) - Di Re, Angelina; Liang, Yi; Gosselink, Martijn Pieter; Ctercteko, Grahame
Abstract: Background: Inflammatory bowel disease (IBD) consists of a spectrum of disorders including ulcerative colitis and Crohn's disease, with a rising incidence worldwide. However, despite this prevalence the etiology of IBD remains uncertain. It has been suggested that an episode of gastroenteritis may precipitate IBD. Methods: Studies were identified using a literature search of Pubmed/Medline and Embase/Ovid. This review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The primary outcome was incidence of new-onset IBD after gastroenteritis. Secondary outcomes included incidence of IBD after bacterial, viral, and parasitic gastrointestinal infections. Results: Eleven studies ( n = 923 608 patients) were included. Four studies assessed patients with gastroenteritis, subsequently developing IBD as the primary outcome. Patients with gastroenteritis had a higher incidence of subsequent IBD but this did not reach statistical significance (odds ratio [OR] 3.81, 95% CI 0.52–27.85, P = .19). Seven studies examined the incidence of antecedent gastroenteritis (primary outcome) in patients with a confirmed diagnosis of IBD, compared to the controlled population. There was no difference between incidence of antecedent gastroenteritis across the 2 population groups (OR 1.07, 95% CI 0.55–2.08, P = .85). There was no association between IBD and bacterial, viral, or parasitic infections. Conclusions: In summary, our meta-analysis has shown that there is considerable heterogeneity in the literature regarding the role of gastroenteritis in the development of IBD. Further higher quality studies need to be performed to ascertain the true nature of this. Lay Summary: The incidence of inflammatory bowel disease (IBD) is rising, however the cause remains unknown. It is suggested that gastroenteritis may lead to IBD. Our study does not demonstrate a definite association between gastroenteritis and IBD, but higher quality studies are needed.